2021
DOI: 10.4314/tjs.v47i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of petroleum hydrocarbons contamination in soils and groundwater using electrical resistivity and hydrochemical methods-Case study: Ayetoro, Osogbo southwestern Nigeria

Abstract: The presence of Petroleum Hydrocarbons (PHCs) in hand-dug wells has become a concern to the residents of Ayetoro area, Osogbo. Consequently, the detection of PHCs was evaluated using, nine Vertical Electrical Soundings (VES) and 2D electrical resistivity tomography surveys. Soil samples collected were analyzed for porosity and permeability. Hand-dug well water samples were screened for PHCs. VES revealed that second layer had high apparent resistivity of 14415.0 Ωm, indicating presence of PHCs that had penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The values of soil resistivity recorded in this study were higher than the values obtained by Odoh et al (2023) for transformer oil-contaminated soils. Similarly, Fakunle et al (2021) reported that the presence of oily components of petroleum products in the soil significantly increased its resistivity. This could be linked to the formation of insulating layers in the soil by the oil, which will reduce the conductivity of electrons in the soil.…”
Section: Electrical Conductivity and Resistivitymentioning
confidence: 89%
See 1 more Smart Citation
“…The values of soil resistivity recorded in this study were higher than the values obtained by Odoh et al (2023) for transformer oil-contaminated soils. Similarly, Fakunle et al (2021) reported that the presence of oily components of petroleum products in the soil significantly increased its resistivity. This could be linked to the formation of insulating layers in the soil by the oil, which will reduce the conductivity of electrons in the soil.…”
Section: Electrical Conductivity and Resistivitymentioning
confidence: 89%
“…According to Yodrot et al (2023), petroleum contamination results in increment of the soil dielectric constant, but a decline in the soil electric field intensity. Fakunle et al (2021) reported in their investigation into the electrical properties of oil-polluted soils that, the soils' electrical resistance ability tends to increase as the oil pollution degree increases. High heavy metals presence in the soil affects its dielectric properties, as the soil permittivity increases considerably with increment in the soil heavy metals concentrations (Dahim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Uguru and Udubra (2021) observed that petroleum products increased the petroleum aromatic hydrocarbons, which can possibly cause serious reduction in the soil electrical conductivity, since petroleum has poor (low) electrical conductivity potential. Similarly, Fakunle et al (2021) studied the impact of oil contamination on the electrical properties of virgin soil; and interestingly, they noted that the soil's resistance increased in a non-linear pattern, as the quantity of the oil in the soil mass increases. Yodrot et al (2023) examined the impact of diesel on soil's electrical properties, and reported that the soil dielectric constant increased unevenly, as the diesel volume in the soil increases; while the electric field intensities of the soil samples declined inconsistently as the diesel content in the soil increases.…”
Section: Introductionmentioning
confidence: 99%